MENGOPTIMALKAN DISTRIBUSI ZAKAT PERTANIAN MELALUI EDUKASI DI DESA LOLO GEDANG - Azhar, Azhar; Regen, Ronal; Mailindra, Wiyan; Bustami, Alek Wissalam (Institut Agama Islam Negeri Kerinci, 2024)
Zakat is a fundamental pillar of Islam that plays a strategic role in reducing economic inequality and improving social welfare. In Indonesia, agricultural zakat has significant potential, considering that the majority of its population works in the agricultural sector. However, awareness among the community, especially farmers, regarding the obligation of agricultural zakat remains low. This community service program aims to increase agricultural zakat literacy in LoLo Gedang Village, where the majority of residents are farmers. This activity included socialization, counseling, and practical demonstrations on the mechanism of agricultural zakat that must be paid based on the type of commodities managed, such as citrus, rice, potatoes, coffee, and cinnamon. The results of this program showed a significant increase in the community's understanding of agricultural zakat, with 85% of participants demonstrating a better understanding after attending the counseling. Furthermore, community participation in paying agricultural zakat increased from 15% to 50%, indicating that zakat education has a direct impact on changing community behavior. This program is expected to be adaptable in other villages with similar conditions, so that agricultural zakat can be optimized to provide social and economic benefits for the community.